Effectiveness of banana leaves extract (Musa paradisiaca L.) for wound healing - Putra, Dimas Ariandi Candra; Lutfiyati, Heni; Pribadi, Prasojo (Universitas Ahmad Dahlan, 2017)
Banana leaves (Musa Paradisiaca, L.) has not been widely used in the treatment purpose of this study was to examine the wound healing activity of the gel of banana leaves (Musa paradiasiaca L.) and determine the most effective concentration for wound healing.Target research is to provide natural wound treatment alternatives. The method used is eksperimental.Prosedur research study began with the identification of a banana leaf, banana leaf extraction, formulation of banana leaf extract gel with a concentration of 1%, 5%, 10% and testing to the test animals were harmed .Animal test are grouped into 5 groups the negative control group (base gel), a positive control (bioplacenton), and 3 groups treatment. Measuring ofÂ diameter wound on day-1 through day 7. The observation was tested by using ANOVA and Post Hoc Tukey HSD. ANOVA test results showed a significant difference between the mean percentage of wound healing all groups Treatment .The result ofÂ Post hoc Tukey HSD at the 95% confidence level showed significant differences in the negative control group when compared to the positive control group and the treatment group gel 5% and 10% .It indicates that the positive control, gel 5% and 10% have a wound healing effect. Positive control group compared with the group treated gel 5% and 10% showed significant differences that the average value of the percentage of wound healing is higher than the positive control treatment group. It means the difference meant that the positive control has better activity. While the group gel 5% when compared with the 10% gel group no significant difference in this case means the group gel 5% with 10% having a comparable effectiveness of wound healing.